Fractional Flow Reserve Relates Stronger to Coronary Plaque Burden Than Nonhyperemic Pressure Indexes - Ruurt A. Jukema; Jorge Dahdal; Nick S. Nurmohamed; Pieter G. Raijmakers; Jos Twisk; Pepijn A. van Diemen; R. Nils Planken; G. Aernout Somsen; Niels J. Verouden; Guus A. de Waard; Paul Knaapen; Ibrahim Danad; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The relationship between fractional flow reserve (FFR), resting full‐cycle ratio (RFR), instantaneous wave‐free ratio (iFR), resting distal pressure/aortic pressure (Pd/Pa), and plaque burden as well as phenotype requires further elucidation. Methods and Results In this single‐center cohort study, patients with suspected coronary artery disease who underwent invasive coronary angiography, including routine hyperemic (FFR) and nonhyperemic invasive pressure (Pd/Pa and iFR or RFR) interrogation and computed coronary tomography angiography were prospectively enrolled. Computed coronary tomography angiography was used to assess percentage atheroma volume (PAV), positive remodeling, and low‐attenuation plaque. Among 241 patients with 556 vessels, FFR correlated stronger to PAV compared with Pd/Pa (r=−0.56; versus r=−0.43; P<0.01) and iFR/RFR (r=−0.47; P=0.04). Vessels with FFR and Pd/Pa discordancy showed higher PAV in case of abnormal FFR (34% versus 14%; P<0.01), whereas vessels with FFR and iFR/RFR discordancy showed similar PAV levels. FFR and iFR/RFR, but not Pd/Pa, were independently associated with the presence of low‐attenuation plaque (β, −0.03, P<0.01; β, −0.03, P=0.01; and β, −0.02, P=0.10, respectively). None of the invasive pressure measurements was independently associated with positive remodeling. Pressure index discordancy was not associated with positive remodeling or low‐attenuation plaque. Conclusions FFR correlated stronger to plaque burden, as defined by PAV, than nonhyperemic pressure indexes. For plaque phenotype, both FFR and iFR/RFR were independently associated with low‐attenuation plaque, whereas none of the invasive pressure indexes was associated with positive remodeling.